Effect of the diffusion temperature on the interaction of clusters with impurity atoms in silicon - Saparniyazova, Z.M.; Ismailov, K.A.; Uteniyazov, A.K.; Kamalov, Kh.U. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
In this paper, the results of studies of the effect of the diffusion temperature on the interaction of clusters of manganese atoms with the sulfur ones have been presented. It has been shown that the electrical parameters of the samples simultaneously doped with sulfur and manganese completely coincide with the parameters of the initial material, i.e., as if they do not contain not only sulfur and manganese, but also thermodonors are not formed. The obtained results make it possible to exclude the possibility of gettering of impurity atoms or formation of some kind of solid solutions, if taking into account the impurity atoms of manganese and sulfur, which complicates their diffusion in the crystal bulk. It has been established that for the initial p-type silicon with the resistivity close to ρ ~ 10 Ω·cm, the diffusion temperature of 1100 °C is the most optimal one to form clusters with the maximum participation of the introduced sulfur and manganese atoms. Наведено результати досліджень впливу температури дифузії на взаємодію кластерів атомів марганцю з атомами сірки. Показано, що електричні параметри зразків, одночасно легованих сіркою і марганцем, повністю збігаються з параметрами вихідного матеріалу, тобто, якби вони не містили не тільки сірку і марганець, але й не утворювали термодонори. Отримані результати дозволяють виключити можливість гетерування домішкових атомів або утворення певного виду твердих розчинів з урахуванням домішкових атомів марганцю і сірки, що ускладнює їх дифузію в об’єм кристала. Встановлено, що для вихідного кремнію р-типу з питомим опором ρ ~ 10 Ω·см температура дифузії 1100 °С є найбільш оптимальною для формування кластерів з максимальною участю введених атомів сірки та марганцю.